Diagnosing RCVS Without the CV: The Evolution of Reversible Cerebral Vasoconstriction Syndrome. (July 2016) - Jacoby, Nuri; Kaunzner, Ulrike; Dinkin, Marc; Safdieh, Joseph
This is a case of a 52-year-old man with a past medical history of 2 episodes of coital thunderclap headaches as well as recent cocaine, marijuana, and pseudoephedrine use, who presented with sudden, sharp, posterior headache associated with photophobia and phonophobia. His initial magnetic resonance imaging (MRI) of the brain, magnetic resonance angiography (MRA) of the head, and magnetic resonance venography (MRV) of the head were all normal as well as a normal lumbar puncture. Given the multiple risk factors for reversible cerebral vasoconstriction syndrome (RCVS), the patient was treated for suspected RCVS, despite the normal imaging. Repeat MRI brain 3 days after hospital admission demonstrated confluent white matter T2 hyperintensities most prominent in the occipital lobes, typical of posterior reversible encephalopathy syndrome (PRES). Repeat MRA of the head 1 day after discharge and 4 days after the abnormal MRI brain showed multisegment narrowing of multiple arteries. This case demonstrates that RCVS may present with PRES on MRI brain and also exemplifies the need to treat suspected RCVS even if imaging is normal, as abnormalities in both the MRI and the MRA may be delayed.